Rheological and rutting evaluation of composite nanosilica/polyethylene modified bitumen - Bala, N. (Institute of Physics Publishing, 2017)
In this research, composite nanosilica/polyethylene modified binder samples were prepared at varying concentration of nanosilica. The modified binder samples are prepared by adding 1, 2 and 3 nanosilica by weight of bitumen in to 6 linear low density polyethylene (LLDPE) polymer modified binder. Effects of nanosilica on physical and rheological properties of composites were investigated through penetration, softening point, temperature susceptibility, dynamic mechanical analysis and rutting resistance evaluations. Results shows that, nanosilica affects the rheological properties of LLDPE modified binder due to decrease in penetration and increase in softening point observed with increase in nanosilica content, this enhances composite binders hardness and resistance to temperature. Temperature susceptibility shows that, composite modified binders are less susceptible to temperature compared to LLDPE modified binder. DSR rheological analysis shows that, nanosilica enhances the composite modified binders properties at intermediate to high temperatures. Also rutting parameter evaluation indicates that composite modified binders have high resistance to rutting deformations due to increase in elastic behavior and stiffness of the composites. © Published under licence by IOP Publishing Ltd.